Indigenismos en el Diccionario de nicaraguanismos (1939) de H. A. Castellón: el campo léxico del mundo vegetal - Martín Cuadrado, Carmen (2024)
This article aims at analysing the indigenous presence, since loanword(s) from indigenous American languages, in the first lexicographical repertoire published in Nicaragua by a Nicaraguan, the Diccionario de nicaraguanismos (1939) by H. A. Castellón. In addition, not only are the words classified according to the Amerindian language of origin, but they are also distributed by lexical fields with the aim of observing in which lexical field indigenism predominates. Finally, due to its productivity, the focus is placed on the lexical field of flora, and the mechanisms used by the author to define the lemma are distinguished. In this sense, the work outlined is intended as a contribution to the study of Nicaraguan lexicography and lexicology, which has been largely neglected in previous research.